Pb‐Based Nanocomposite Anodes: New High‐Performance Pb‐Based Nanocomposite Anode Enabled by Wide‐Range Pb Redox and Zintl Phase Transition (Adv. Funct. Mater. 2/2021). (11th January 2021) - Han, Jinhyup; Park, Jehee; Bak, Seong‐Min; Son, Seoung‐Bum; Gim, Jihyeon; Villa, Cesar; Hu, Xiaobing; Dravid, Vinayak P.; Su, Chi Cheung; Kim, Youngsik; Johnson, Christopher; Lee, Eungje
Abstract : The tremendous growth in Li‐ion batteries puts pressure on supply chains leading to the need to invest in recyclable processes. In article number 2005362, Eungje Lee, Seong‐Min Bak, and co‐workers synthesize a potentially recyclable lead‐based anode (Pb anode) via high‐energy ball‐milling production of a self‐limiting oxide coated lead core embedded within a carbon matrix. Electrochemical cycling performance is good, demonstrating 500 mAhg −1 with over 92% retention at 100 cycles.